2016
DOI: 10.1142/s0219530515400023
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of bi-cluster flocking for agent-based models with unit speed constraint

Abstract: We study the emergence of bi-cluster flocking for a generalized Justh–Krishnaprasad (J–K) model and the Cucker–Smale (C–S) model with the unit speed constraint. We provide a sufficient framework for the emergence of bi-cluster flocking in terms of initial configurations and communication weights between agents. Our analytical results on bi-cluster flocking illustrate that the spatial-decay rate of communication weights is transferred to the temporal decay rate toward the bi-cluster flocking configuration. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In this small coupling strength regime, there might be local flocking(or multi-cluster flocking). Recently this issue has been addressed in a series of papers [16,17,39,40]. [1], C-S model with a singular communication weight is considered.…”
Section: )mentioning
confidence: 99%
“…In this small coupling strength regime, there might be local flocking(or multi-cluster flocking). Recently this issue has been addressed in a series of papers [16,17,39,40]. [1], C-S model with a singular communication weight is considered.…”
Section: )mentioning
confidence: 99%
“…For a small coupling strength κ 1, bi-cluster and multi-cluster flockings can emerge from some initial configurations. It has been shown that local flocking, in particular bi-cluster flocking, can emerge from some well-prepared configurations close to bi-cluster configurations [12,13].…”
Section: Definition 23 For a Given Initial Configurationmentioning
confidence: 99%
“…For example, for a long-range communication weight with an infinite L 1 -norm, mono-cluster(global) flocking occurs for any initial configurations. In contrast, for a short-range communication weight, numerical simulations in [12,13] illustrate that mono-cluster(global) flocking does not occur for some initial configurations. There are also interesting works on optimal control of Cucker-Smale model [3,5,7].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, in Refs. [9,10], it has been shown that local flocking, in particular bicluster flocking, can emerge from some well-prepared configurations close to bicluster configurations.…”
mentioning
confidence: 99%